Myocyte enhancer factor 2D promotes colorectal cancer angiogenesis downstream of hypoxia-inducible factor 1α. (1st August 2017) - Xiang, Junyu; Sun, Hui; Su, Li; Liu, Limei; Shan, Juanjuan; Shen, Junjie; Yang, Zhi; Chen, Jun; Zhong, Xing; Ávila, Matías A.; Yan, Xiaochu; Liu, Chungang; et al.
Abstract: Myocyte enhancer factor 2D (MEF2D) is involved in many aspects of cancer progression, including cell proliferation, invasion, and migration. However, little is known about the role of MEF2D in tumor angiogenesis. Using clinical specimens, colorectal cancer (CRC) cell lines and a mouse model in the present study, we found that MEF2D expression was positively correlated with CD31-positive microvascular density in CRC tissues. MEF2D promoted tumor angiogenesis in vitro and in vivo and induced the expression of proangiogenic cytokines in CRC cells. MEF2D was found to be a downstream effector of hypoxia-inducible factor (HIF)-1α in the induction of tumor angiogenesis. HIF-1α transactivates MEF2D expression by binding to the MEF2D gene promoter. These results demonstrate that the HIF-1α/MEF2D axis can serve as a therapeutic target for the treatment of CRC. Highlights: MEF2D level is positively correlated with microvascular density in CRC tissue. MEF2D promotes angiogenesis in vitro and in vivo by inducing angiogenic cytokines. MEF2D acts downstream of HIF-1α in the hypoxic tumor microenvironment. The HIF-1α/MEF2D axis can serve as a therapeutic target for CRC treatment.